Relevansi Tasawuf dalam Mengurangi Kecemasan Remaja pada Saat Menghadapi Tes Masuk Perguruan Tinggi - Karimatus Sa’diyah; Robingatun Robingatun; Yuli Darwati; Ach. Shodiqil Hafil (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study was to find out: 1) descriptions and factors that influence adolescents' anxiety during college entrance tests: 2) the relevance of Sufism in reducing adolescents' anxiety in facing college entrance tests. This research is a literature review. The data in this study were extracted from various sources that discuss anxiety in facing college entrance tests and Sufism. The data collected was then analyzed qualitatively. The results of this study indicate: 1) the fact that adolescents experience anxiety when facing college entrance tests. Technology-based college entrance tests and high societal standards as a measure of success in learning, create excessive anxiety and have an impact on exam results: 2) Anxiety that affects all elements of humanity can be overcome with tasawuf therapy. Sufism therapy is also easy to do and relevant for all ages.